K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 8 2021

\(15m^3-5m^2+7m\left(1-3m\right)\)

\(=5m^2\left(3m-1\right)-7m\left(3m-1\right)\)

\(=\left(5m^2-7m\right)\left(3m-1\right)=m\left(5m-7\right)\left(3m-1\right)\)

24 tháng 11 2021

5m^2 - 5mn + 3m - 3n

= 5m . ( m - n ) + 3 . ( m - n )

= ( m - n ) . ( 5m + 3 )

24 tháng 11 2021

5m^2 - 5mn + 3m - 3n

= 5m(m-n) + 3(m-n)

= (m-n)(5m+3)

23 tháng 3 2017

\(3m^2-2m-1\)

\(=3m^2-3m+m-1\)

\(=3m\left(m-1\right)+\left(m-1\right)\)

\(=\left(m-1\right)\left(3m+1\right)\)

23 tháng 3 2017

\(3m^2-2m-1\)

\(=3m^2+m-3m-1\)

\(=\left(3m^2+m\right)-\left(3m+1\right)\)

\(=m\left(3m+1\right)-\left(3m+1\right)\)

\(=\left(m-1\right)\left(3m+1\right)\)

7 tháng 11 2021

1a) \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)

b) \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)

7 tháng 11 2021

\(a,=-\left(x-1\right)^3\left[=\left(1-x\right)^3\right]\\ b,=\left(1-x\right)^3\)

26 tháng 12 2021

\(-8x^3+1=1^3-\left(2x\right)^3=\left(1-2x\right)\left(1+2x+4x^2\right)\)

10 tháng 8 2023

Bài 2:

1)  \(x^2-4x+4=\left(x-2\right)^2\)

2) \(x^2-9=x^2-3^2=\left(x-3\right)\left(x+3\right)\)

3) \(1-8x^3=\left(1-2x\right)\left(1+2x+4x^2\right)\)

4) \(\left(x-y\right)^2-9x^2=\left(x-y\right)^2-\left(3x\right)^2=\left(x-y-3x\right)\left(x-y+3x\right)=\left(-2x-y\right)\left(4x-y\right)\)

5) \(\dfrac{1}{25}x^2-64y^2=\left(\dfrac{1}{5}x-8y\right)\left(\dfrac{1}{5}x+8y\right)\)

6) \(8x^3-\dfrac{1}{8}=\left(2x-\dfrac{1}{2}\right)\left(4x^2+x+\dfrac{1}{4}\right)\)

10 tháng 8 2023

mình cảm ơn nha

 

26 tháng 3 2018

a3m+2a2m+am = am(a2m+2am+1) = am[(am)2+2am+1] = am(am+1)2

26 tháng 3 2018

Ta có :

a3m+2a2m+am 

= am(a2m+2am+1)

= am[(am)2+2am+1]

= am(am+1)2

3 tháng 8 2015

Bài 1 :

\(x^2-6x+8=x^2-2x-4x+8=x\left(x-2\right)-4\left(x-2\right)=\left(x-4\right)\left(x-2\right)\)

Bài 2 :

 \(x^8+x^7+1=x^8+x^7+x^6+x^5+x^4+x^3+x^2+x+1-x^6-x^5-x^4-x^3-x^2-x\)

\(=x^6\left(x^2+x+1\right)+x^3\left(x^2+x+1\right)+x^2+x+1-x^4\left(x^2+x+1\right)-x\left(x^2+x+1\right)\)

=\(\left(x^2+x+1\right)\left(x^6+x^3+1-x^4-x\right)\)

Tick đúng nha 

1 tháng 8 2021

X^2-6+8